Tertiary lymphoid structures predict survival and response to neoadjuvant therapy in locally advanced rectal cancer - Qianyu Wang; Wentao Zhong; Xiaofei Shen; Zechen Hao; Meng Wan; Xiaopeng Yang; Ran An; Hongyan Zhu; Huiyun Cai; Tao Li; Yuan Lv; Xing Dong; et al. (npj Precision Oncology, 2024)
Abstract Tertiary lymphoid structure (TLS) contributes to the anti-tumor immune response, and predicts the prognosis of colorectal cancer patients. However, the potential impact of TLS in shaping the immune status of rectal adenocarcinoma, and the intrinsic relationship between TLS and neoadjuvant therapies (neoTx) remain unclear. We performed hematoxylin-eosin staining, immunohistochemical and biomolecular analyses to investigate TLS and tumor-infiltrating lymphocytes (TILs) in 221 neoTx-treated and 242 treatment-naïve locally advanced rectal cancer (LARC) patients. High TLS density was significantly associated with the absence of vascular invasion, a lower neutrophil-to-lymphocyte ratio, increased TLS maturity, a longer recurrence-free survival (RFS) (hazard ratio [HR] 0.2985 95% confidence interval [CI] 0.1894–0.4706, p < 0.0001) and enhanced infiltration of adaptive immune cells. Biomolecular analysis showed that high TLS-score was strongly associated with more infiltration of immune cells and increased activation of immune-related pathways. TLS+ tumors in pre-treatment specimens were associated with a higher proportion of good respond (62.5% vs. 29.8%, p < 0.0002) and pathological complete remission (pCR) (40.0% vs. 11.1%, p < 0.0001), and significantly increased RFS (HR 0.3574 95%CI 0.1489–0.8578 p = 0.0213) compared with TLS- tumors in the neoTx cohort, which was confirmed in GSE119409 and GSE150082. Further studies showed that neoTx significantly reduced TLS density and maturity, and abolished the prognostic value of TLS. Our study illustrates that TLS may have a key role in mediating the T-cell-inflamed tumor microenvironment, which also provides a new direction for neoTx, especially neoadjuvant immunotherapy, in LRAC patients.